CLINICAL AND ANAMNESTIC RISK FACTORS FOR INFERTILITY IN PCOS AND EXTERNAL GENITAL ENDOMETRIOSIS - Светлана Ивановна Елгина; Лариса Николаевна Данилова; Олеся Юрьевна Михальцова; Николай Владимирович Журин; Елена Владимировна Рудаева; Кира Борисовна Мозес; Вадим Гельевич Мозес; Наталья Степановна Черных (The Publishing House Medicine and Enlightenment, 2024)
There is evidence in the scientific literature that a number of patients with infertility have a combination of two gynecological nosologies: genital endometriosis and polycystic ovary syndrome. Both of these diseases are characterized by high prevalence and frequency, which reaches 10-70 %. The study of the problem of infertility against the background of a combination of PCOS and NGE determines the practical and theoretical significance of the research.